Clump Structure, Standing Stock Biomass and Carbon Sequestration - Jijeesh, CM; Thomas, Kuruvilla; Seethalakshmi, KK (Indian Forester, 2020)
Munrochloa ritchiei (Munro) M. Kumar and Remesh, is a perennial, sympodial bamboo species endemic to Western Ghats of Kerala. The present study focuses on the clump structure, standing stock biomass and carbon storage of this species. Clump structure of the species was recorded in the sample plots and the destructive sampling was carried out to study biomass production and carbon sequestration potential. During the first and second observations the average number of culms was found to be 13,801.2 and 20,154.96, respectively. The distribution of culms in different height class followed a normal distribution whereas; Weibull distribution was the best fit for girth classes. The standing stock biomass of M. ritchiei was 70.6±37.9 t ha-1 and culms and rhizome contributed maximum towards total biomass. Carbon sequestration potential of the species was 30.1±14.9 t h-1. Total soil carbon stock under the bamboo stand up to a depth of 60 cm was to the tune of 84.799±19.202 t ha-1. The present study exhibits a unique bamboo species which can play major role in the climate change mitigation and provide more opportunity for livelihood on a sustainable basis.